2008
DOI: 10.2137/145960606778644511
|View full text |Cite
|
Sign up to set email alerts
|

Polymer coated turnip rape seed did not facilitate early broadcast sowing under Finnish growing conditions

Abstract: An alternative sowing time for summer turnip rape (Brassica rapa L. var. oleifera subvar. annua) and canola rape (Brassica napus L. var. oleifera subvar. annua) was investigated under northern European growing conditions, where the growing season is very short and seedling establishment in spring is difficult. Using a method termed carrier technology, seeds of spring canola were coated with polymer and sown in winter or early spring. Two types of polymer were tested: water-impervious Poligen  WE3 (polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…2006; Medeiros et al. 2006), the polymers could have a negative impact on germination (Peltonen‐Sainio et al. 2006; Mangold and Sheley 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006; Medeiros et al. 2006), the polymers could have a negative impact on germination (Peltonen‐Sainio et al. 2006; Mangold and Sheley 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid germination and emergence will allow the coated seeds to establish quickly. Even though many researches reported that germination of seeds coated with hygroscopic polymers enhanced germination (Arsego et al 2006;Medeiros et al 2006), the polymers could have a negative impact on germination (Peltonen-Sainio et al 2006;Mangold and Sheley 2007).…”
Section: Residual Effects Of Coating Alga and Spore On Plant Growth Amentioning
confidence: 99%
“…Polymer coatings are used in the agriculture seed industry to improve hybrid corn production and for relay cropping (Lessiter, 2000). In addition, polymer‐coated seed offers the possibility of extending the growing season of spring crops in cold regions by sowing seed in winter or earlier in the spring (Gesch and Archer, 2005; Peltonen‐Sainio et al, 2006). Temperature‐activated polymers change structure at a critical temperature; this change in structure also causes a change in permeability of the polymer (Hicks et al, 1996).…”
mentioning
confidence: 99%
“…oleifera DC.) (Peltonen-Sainio et al 2006), sowing is best carried out when soil temperatures are c. 10°C (Pahkala 2003). Combining an optimal temperature regime with other conditions that favour germination is challenging.…”
mentioning
confidence: 99%
“…Winter sowing would lighten the workload and provide moist soils for germination, but winter crop types lack sufficient winter hardiness for Finnish conditions. However, using carrier technology, by sowing polymer-coated seeds during the preceding autumn, winter or very early spring (Kirkland & Johnson 2000;Karamanos et al 2002;Clayton et al 2004;Johnson et al 2004), did not prove successful under Finnish conditions when combined with broadcast sowing (Peltonen-Sainio et al 2006). Therefore, the problems in turnip rape production that are linked with uncertainty about seedling establishment need other solutions.…”
mentioning
confidence: 99%